Vosstonovlenie mysecnoj rabotosposobnosti kak faktor dostizenija vysokich sportivnych rezul'tatov - Loscilov, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The author has studied the influence of induction of the variable (50 hertz) magnetic field on the activity of neuro-muscular apparatus of a human being in conditions of local and general(common) exhaustion. He has come to the following conclusions: - the variable of the magnetic field of industrial frequency influences muscular serviceability, authentically increas-ing it in conditions of local and general deep exhaustion. - the parameters of electromyogram at optimum loadings can serve as independent criteria of the stimation of ser-viceability or exhaustion. - the quantitative changes of parameters of the electromyogram and pulse at influence of the magnetic field at the given level allow to draw a conclusion, that this influence does not cause appreciable deviations in neurohumoral control. - the constant of the magnetic field with induction of 75 and 400 gausses does not render influence on the rehabili-tation of the muscular serviceability of a person.